How much would irrigation increase maize production in Brazil? - Luís Alberto Silva Antolin; Evandro Henrique Figueiredo Moura da Silva; Alencar Junior Zanon; Bruna San Martin Rolim Ribeiro; Fabio Ricardo Marin (Scientia Agricola)
ABSTRACT Maize production in Brazil is notable for its high potential for agricultural expansion and extensive cropland areas. This study evaluated the current yield gap (Yg) in Brazilian maize production and investigated the potential impact of irrigation on closing this gap. Field experiments were conducted in three key maize-producing regions in Brazil to calibrate a crop model and obtain reliable data on yield potential (Yp) and water-limited yield potential (Yw) across different environments. Data on river basin flows were employed to ensure that irrigation would not result in the depletion of water resources for other uses. Our findings suggest that Brazil’s average actual yield (Ya) is 55.4 % below the Yp. It was determined that increasing irrigation levels is a viable method for achieving the potential maize yield without compromising available water resources. The average Yg is approximately 5.2 Mg ha–1, indicating a potential production increase of 41.9 % without expanding cropland areas. Strategic planning is essential to balance increased production and expanded irrigation, particularly to avoid impacting regions with water scarcity. It is underscored that the focus should be on areas with sufficient water resources to close Brazil’s current maize Yg. The results from this study offer valuable data for decision-makers and policymakers to enhance maize production sustainably.